Epidemiology of Vancomycin-Resistant Enterococcus faecium and Enterococcus faecalis Colonization in Nursing Facilities. (6th January 2020) - Davis, Elyse; Hicks, Liam; Ali, Ihsan; Salzman, Elizabeth; Wang, Joyce; Snitkin, Evan; Gibson, Kristen; Cassone, Marco; Mody, Lona; Foxman, Betsy
Abstract: Background: Vancomycin-resistant Enterococcus faecium and Enterococcus faecalis frequently colonize nursing facility (NF) residents, creating opportunities for vancomycin-resistant Enterococcus (VRE) transmission and dissemination of mobile genetic elements conferring antimicrobial resistance. Most VRE studies do not speciate; our study addresses this lack and compares the epidemiology of E faecium and E faecalis . Methods: We enrolled 651 newly admitted patients from 6 different NFs and collected swabs from several body sites at enrollment, 14 days, 30 days, and monthly thereafter for up to 6 months. The VRE were speciated using a duplex polymerase chain reaction. We used multinomial logistic regression models to compare risk factors associated with colonization of E faecium and E faecalis. Results: Overall, 40.7% were colonized with E faecium, E faecalis, or both. At enrollment, more participants were colonized with E faecium (17.8%) than E faecalis (8.4%); 3.2% carried both species. Enterococcus faecium was carried twice as long as E faecalis (69 days and 32 days, respectively), but incidence rates were similar ( E faecium, 3.9/1000 person-days vs E faecalis, 4.1/1000 person-days). Length of stay did not differ by species among incident cases. Residents who used antibiotics within the past 30 days had a greater incidence of both E faecium (odds ratio [OR] = 2.89; 95% confidence interval [CI], 1.82–4.60) and E faecalis (OR = 1.80; 95% CI, 1.16–2.80); device use was most strongly associated with the incidence of E faecium colonization (OR = 2.01; 95% CI, 1.15–3.50). Conclusions: Recent increases in vancomycin-resistant E faecium prevalence may reflect increased device use and longer duration of carriage.